2010
DOI: 10.1111/j.1365-2958.2009.06970.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivorequirement of selenophosphate for selenoprotein synthesis in archaea

Abstract: SummaryBiosynthesis of selenocysteine, the 21st proteinogenic amino acid, occurs bound to a dedicated tRNA in all three domains of life, Bacteria, Eukarya and Archaea, but differences exist between the mechanism employed by bacteria and eukaryotes/archaea. The role of selenophosphate and the enzyme providing it, selenophosphate synthetase, in archaeal selenoprotein synthesis was addressed by mutational analysis. Surprisingly, MMP0904, encoding a homologue of eukaryal selenophosphate synthetase in Methanococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 64 publications
(140 reference statements)
1
55
0
2
Order By: Relevance
“…Therefore, an experiment was designed to clarify whether gene conversion exists in methanogenic archaea and how efficient it is in genome equalization. We made use of a heterozygous mutant that was recently constructed (44). The attempt to replace the selenophosphate synthetase-encoding gene (selD) of M. maripaludis S2 with a puromycin resistance cassette (pacN) revealed that the selD gene is essential and cannot be completely removed from the cell.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, an experiment was designed to clarify whether gene conversion exists in methanogenic archaea and how efficient it is in genome equalization. We made use of a heterozygous mutant that was recently constructed (44). The attempt to replace the selenophosphate synthetase-encoding gene (selD) of M. maripaludis S2 with a puromycin resistance cassette (pacN) revealed that the selD gene is essential and cannot be completely removed from the cell.…”
Section: Resultsmentioning
confidence: 99%
“…The attempt to replace the selenophosphate synthetase-encoding gene (selD) of M. maripaludis S2 with a puromycin resistance cassette (pacN) revealed that the selD gene is essential and cannot be completely removed from the cell. Therefore, selection in the presence of puromycin yielded a strain (designated SkoD4) that contained two different genomes; the majority of genome copies carried the pacN gene at the selD locus, while a few genome copies retained the native selD gene at this site (44). The strain was used to inoculate four different cultures, which were incubated under four different conditions: (i) in the presence of the "normal" puromycin concentration (2.5 g ml Ϫ1 ), which is totally inhibitory for the wild-type (45); (ii and iii) in the presence of two lower puromycin concentrations (0.6 and 0.15 g ml Ϫ1 , respectively); and (iv) in the absence of puromycin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations